Analisis Pembelajaran Bahasa Indonesia di Sekolah Dasar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
Learning is an activity to educate students at school which aims to make science acceptable and well understood. Through the learning process, students are expected to experience positive changes, both in terms of knowledge, attitudes, and skills. One of the learning processes that has a great influence on the lives of students is learning Indonesian. Learning Indonesian is very important because it functions as the main means of communication in daily life, both orally and in writing. With good Indonesian language skills, students will find it easier to express ideas, understand information, and interact effectively with the surrounding environment. Therefore, Indonesian learning in elementary schools must be designed in a systematic, interesting, and in accordance with the characteristics of students. In addition to clear goals, appropriate strategies and solutions are also needed to overcome various difficulties that arise, such as low interest in learning, limited vocabulary, and lack of reading and writing comprehension. These efforts are expected to be able to improve the quality of Indonesian learning optimally.